Sosialisasi dan Penerapan Aspek Keselamatan dan Kesehatan Kerja (K3) pada Mata Kuliah Praktikum Teknologi Ototronik Jurusan Pendidikan Vokasional Teknologi Otomotif - Maulana, Fajar; Putra, Meiyaldi Eka; Irawan, Teguh (Journal of Social and Community Service, 2025)
The socialization and implementation of Occupational Safety and Health (OSH) aspects in the Ototronics Practicum Course at the Department of Vocational Education in Automotive Technology, Universitas Lancang Kuning, represent a tangible form of community service contribution aimed at improving human resource quality, particularly among students. The application of OSH principles in practicum activities significantly influences students’ learning outcomes. This study employed a descriptive-correlational approach to examine the relationship between OSH implementation and practicum results. Analysis showed a correlation coefficient (r) of 0.753, exceeding the r-table value of 0.266, and a t-value of 5.231, surpassing the t-table value of 1.673. These findings indicate a significant positive relationship at the 5% level. Thus, understanding and applying OSH principles support a more effective learning process and contribute meaningfully to improving students’ practicum performance.